2016
DOI: 10.1177/1077558716673459
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Care Management: An Analysis of Recent AHRQ Research

Abstract: Care management (CM) is a promising team-based, patient-centered approach "designed to assist patients and their support systems in managing medical conditions more effectively." As little is known about its implementation, this article describes CM implementation and associated lessons from 12 Agency for Healthcare Research and Quality-sponsored projects. Two rounds of data collection resulted in project-specific narratives that were analyzed using an iterative approach analogous to framework analysis. Inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
(25 reference statements)
0
14
0
Order By: Relevance
“…31 ) Furthermore, EHRs facilitate communication among medical staff and organizations and provide structured coordination and documentation of the medical services provided. 32 ) Therefore, GSC performed within 48 hours of hospitalization using the EHRs of all inpatients aged 65 years or older is expected to be efficient.…”
Section: Discussionmentioning
confidence: 99%
“…31 ) Furthermore, EHRs facilitate communication among medical staff and organizations and provide structured coordination and documentation of the medical services provided. 32 ) Therefore, GSC performed within 48 hours of hospitalization using the EHRs of all inpatients aged 65 years or older is expected to be efficient.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in family need perceptions among the three groups of study participants also existed in "helping with the patient care" (p=0.009), shown in Table 5. The value of this family need of Saudi parents should be valued more since the role of the family members care providers is widely accepted [38] and requires continuous support.…”
Section: Discussionmentioning
confidence: 99%
“…Methodologically, these studies were principally qualitative ( 7 , 35 38 , 40 , 41 , 44 , 47 , 49 , 51 , 54 56 ), with a few using mixed methods ( 6 , 39 , 42 , 45 , 48 , 50 , 53 ) and two randomized control trials ( 28 , 46 ). Furthermore, two reviews ( 24 , 52 ) were included about diabetes that provided some insights into the organizational context necessary for team-based care, although they were not specifically about organizational conditions.…”
Section: Resultsmentioning
confidence: 99%
“…At a macro-level studies identified organizational factors focused on the capacity to exchange clinical and billing data across providers to improve coordination. Significant attention is also provided to the role of technology at the meso level including access to an electronic medical record (EMR), a data manager, technical resources, data analytics capacity, patient registries, hospital admissions data, compliance, and quality metrics ( 6 , 7 , 24 , 28 , 38 , 46 , 47 , 49 , 52 , 55 , 56 ). At the micro-level a U.S. Agency for Healthcare Research and Quality review ( 59 ) on the implementation of its diabetes care models provides significant guidance related to technology supports for the team citing EMRs and IT that enable and support “communication among care team members (e.g., via electronic patient care plans); managing patient registries; coordinating, and documenting services to be delivered in a structured manner; reminding patients about appointments or contacting patients who were lost to follow-up; creating and tracking patients' plans of care and progress toward their goals; identifying additional “triggers”.” Further research needs to be carried out in low income settings countries and communities with low income patients.…”
Section: Resultsmentioning
confidence: 99%